Analysis of problem-solving ability: Pólya's strategy and positive attitude - Wenny Fitria; Rudi Susilana; Nanang Priatna (Himpunan Pengembang Kurikulum Indonesia, 2024)
Problem-solving is essential for individuals to face various challenges in the 21st century. Therefore, problem-solving has become a primary goal in mathematics curricula worldwide. However, despite its importance, problem-solving remains one of the most challenging aspects to grasp in mathematics education. Several studies have shown that appropriate strategies and a positive attitude toward problem-solving can help improve students' problem-solving abilities. In this study, the author will examine the implementation of Pólya's mathematical problem-solving strategy. Additionally, the study will explore students' attitudes toward problem-solving and how these attitudes influence their performance. Finally, the research will assess the combined impact of Pólya's strategy and students' attitudes on their problem-solving abilities. This study employs a qualitative approach using content analysis methods. The results show that the top ten students from one of the best schools in Siak Regency still struggle to solve simple problems. This failure is attributed to inappropriate strategies and a lack of a positive attitude toward problem-solving. The study concludes that mastering problem-solving strategies and fostering a positive attitude are crucial for students to become effective problem solvers. Abstrak Pemecahan masalah adalah keterampilan penting yang dibutuhkan individu untuk menghadapi berbagai tantangan di abad ke-21, sehingga menjadi tujuan utama dalam kurikulum matematika di banyak negara. Meskipun penting, aspek ini tetap menjadi bagian yang paling sulit dipahami dalam pendidikan matematika. Penelitian terdahulu menunjukkan bahwa secara terpisah, strategi yang tepat serta sikap positif terhadap pemecahan masalah, dapat meningkatkan kemampuan pemecahan masalah siswa. Penelitian ini bertujuan untuk mengkaji penerapan strategi Pólya dalam pemecahan masalah matematika. Selain itu, penelitian ini juga akan mengeksplorasi sikap siswa terhadap pemecahan masalah dan bagaimana sikap tersebut mempengaruhi kinerja mereka. Akhirnya, penelitian ini akan menilai dampak gabungan dari strategi Pólya dan sikap siswa terhadap kemampuan pemecahan masalah mereka. Penelitian ini menggunakan pendekatan kualitatif dengan metode analisis konten. Hasilnya menunjukkan bahwa sepuluh siswa terbaik di salah satu sekolah terkemuka di Kabupaten Siak masih kesulitan menyelesaikan masalah sederhana. Kesulitan ini disebabkan oleh penggunaan strategi yang kurang tepat dan sikap positif yang rendah terhadap pemecahan masalah. Penelitian ini menyimpulkan bahwa penguasaan strategi pemecahan masalah dan pengembangan sikap positif secara bersamaan sangat penting agar siswa dapat menjadi pemecah masalah yang lebih efektif. Kata Kunci: heuristic pólya; pemecahan masalah matematika; sikap positif